Identification and Characterization of Cassava Mosaic Begomoviruses in Non-crop Plants from Unguja and Pemba Islands - Mwakosya, Joseph A.; Temu, Gladness E.; Ndunguru, Joseph C. (Tanzania Journal of Science, 2021)
Cassava mosaic disease caused by cassava mosaic begomoviruses (CMBs) remains one of the major constraints to cassava production since it causes yield losses up to 100%. Researches showed that some of CMBs infecting cassava plants may be coming from non-crop plants. This study intended to identify and characterize CMBs isolated from non-crop plant species in Unguja and Pemba Islands. A total of 108 viral symptomatic and asymptomatic non-crop leaf samples were collected using stratified sampling. DNA was extracted by using CTAB protocol followed by polymerase chain reaction using universal and specific primers for cassava mosaic begomoviruses identification. Results showed that, among eleven samples that were amplified, four were African cassava mosaic viruses (ACMV) and seven were East African cassava mosaic viruses (EACMV). DNA sequencing by Sanger method showed 97–99% similarities with isolates of ACMV and EACMV reported elsewhere in Africa. Using RbcL and MatK plant barcode genes, Datura stramonium, Solanum melongena and Solanum incanum were found associated with ACMV, while Senna occidentalis, Sida acuta and Ricinus communis harboured EACMV. These findings are a key in understanding the epidemiology of cassava mosaic disease and are potential in the development of sustainable management strategies for this disease. Keywords: Begomoviruses, Cassava mosaic disease, East African cassava mosaic virus, Non crop plants. Keywords: Begomoviruses, Cassava mosaic disease, East African cassava mosaic virus, Non crop plants.